Alaca Höyük Geç Tunç Çağı yapı kompleksinin /tapınak/tapınak-saray/saray) tanımı = Definition of Alaca Höyük Late Bronze Age building complex (temple/temple-palace/palace). - Baltacıoğlu, Hatçe. (Ankara)
s. 23-39